The effect of an intraorifice barrier and base under coronal restorations on the healing of apical periodontitis: a randomized controlled trial. (3rd November 2019) - Kumar, G.; Tewari, S.; Sangwan, P.; Tewari, S.; Duhan, J.; Mittal, S.
Abstract: Aim: To evaluate the effect of intraorifice barriers and bases on the healing of apical periodontitis following root canal treatment in mandibular molars. Methodology: A total of 120 permanent mandibular molars with necrotic pulps and periapical radiolucencies (PAI score ≥ 3) were recruited. Root canal treatment was performed in all teeth using a standard protocol, following which they were randomly allocated to one of the three treatment groups: intraorifice barrier group: coronal 3‐mm gutta‐percha was removed and replaced with glass–ionomer cement (GIC) barrier. The floor of the pulp chamber was then sealed with 2‐mm‐thick GIC base followed by final composite resin restoration; base group: received 2‐mm‐thick GIC base before placement of composite resin restoration; and control group: had pulp chamber entirely filled with composite resin only. Follow‐up was done at 3, 6, 9 and 12 months. Combination of clinical and radiographic parameters were used to assess treatment outcome. The data were analysed using Kruskal–Wallis, chi‐square and Wilcoxon signed‐rank tests and logistic regression analysis. Results: At the end of 12 months, the base group had the most favourable healing (97.1%), whilst the control group had the least favourable healing (83.8%). The intraorifice barrier group had healing of 92.1%. However, there was no significant difference in healing between groups at the end of the follow‐up period ( P > 0.05). Additional subgroup analysis revealed a nonsignificant effect of periodontal status and root filling level on periapical healing. Conclusion: The use of an additional barrier under permanent restorations did not significantly improve the outcome of primary root canal treatment in posterior teeth after 12 months. However, its influence in the long term requires further evaluation.